Mexico’s Higher Education Students’ Experience During the Lockdown due to the COVID-19 Pandemic - Zapata-Garibay, Rogelio; González-Fagoaga, Jesús Eduardo; Meza-Rodríguez, Elsa B.; Salazar-Ramírez, Edgar; Plascencia-López, Ismael; González-Fagoaga, Clara Judith (Frontiers in Education, 2021)
Transition from face-to-face to distant courses in Mexico represented a challenge for teachers, students, and parents from all the education levels. Mexican federal government declared Phase 2 of the plan to reduce COVID-19 spread on March 24, 2020. In some states were anticipate mobility restriction measures from March 17, included the education system. On April 13, were reactivated educational activities in the remote mode exclusively and could extend this situation until the end of the 2020-2021 cycle if health conditions do not improve. Derived from the conditions of technological adaptation and digital connectivity in the country, neither the universities nor the professors and students were prepared to implement the emergency remote teaching strategy (ERT). The purpose of this cross-sectional study is to investigate the experiences of graduate and undergraduate students concerning the change from face-to-face to the ERT modality in the health emergency context due to the COVID-19 outbreak. We collected data from 660 students from 38 universities and 22 states across the country. The study investigated online courses previous experience, technological tools use, barriers faced during the new teaching-study modality, current use of educational and technological tools, and some physical and mental health indicators. As a result, we found problems related to time management of their work activities and the balance of time between home and school activities. In the same way, the perception about the study days, which they felt strenuous. More than half of all students reported Internet connection problems. Students from private universities declared greater use of technological tools. Students from public universities expressed greater difficulties following the professors’ instructions, perceived less attention from the professors, considered that the change to online courses was difficult, and felt overwhelmed by the professors or the courses’ technological skills. Students in the first two years of University reported a higher proportion having felt the most strenuous study days, having had difficulties following the professors’ instructions, and considered that the distance modality change was hard. Finally, all the students declared that the expenses increased in their home in the highest proportion were electricity, mobile phone data, and Internet service.